Before I do : a novel [large type] - Cousens, Sophie (Center Point Large Print, 2023)
"Head-in-the-stars Audrey is about to marry down-to-earth Josh. Though they are polar opposites, they have a healthy, stable relationship; Josh is just what Audrey needs. But romance should be unpredictable and full of fireworks, and as the big day approaches, Audrey's found herself wondering if Josh really is "The One." So, when Josh's sister shows up to the rehearsal dinner with Fred, Audrey's "What If? Guy" -- the man she met six years ago and had one amazing day with -- Audrey finds herself torn. Surely Fred's appearance the night before she is due to get married can't be a coincidence. And when everything that could go wrong with the wedding starts to go wrong, Audrey has to ask herself: Is fate trying to stop her from making a huge mistake? Or does destiny just have a really twisty sense of humor?"--